Perancangan Sistem Pemantauan Suhu, Kelembaban, Asap, Kebakaran, Kecepatan Angin dan Arah Angin Berbasis SMS di Lahan Pertanian UNTIRTA - Irma Saraswati; Alimuddin Alimuddin; Sobriansyah Irwan; Muchtar Ali Setyo Yudono (MEDIKA TRADA, 2025)
Farm fires are a major cause of agricultural loss, leading to the destruction of millions of hectares of farmland. In Indonesia alone, the financial losses due to farm fires were estimated at 221 trillion rupiah in 2015. This study proposes the development of an early fire detection and environmental monitoring system that integrates MQ-7 and photodiode sensors for smoke and fire detection, along with additional sensors for monitoring temperature, humidity, wind speed, and wind direction. The system utilizes Short Message Service (SMS) for communication, which was selected due to its low cost, extensive coverage, and ability to facilitate rapid responses during emergencies. Sensor testing revealed that the temperature and humidity sensors (DHT11) exhibited a temperature deviation of 0.37°C and a humidity error of 2 Percent. The photodiode sensor successfully detected fire at distances of up to 150 cm, especially at night, under low light intensity conditions (0-10 Lux). The GSM communication module showed an average response time of 2 seconds, with a deviation range of 1 to 4 seconds between the sending and receiving of SMS messages. The system demonstrated its effectiveness in detecting fire and monitoring environmental parameters, providing real-time alerts every 10 minutes via SMS. This system offers a reliable, cost-effective solution for early fire detection and continuous environmental monitoring, enabling timely intervention to mitigate farm fire risks.